COproduction VALUE creation in healthcare service (CO-VALUE): an international multicentre protocol to describe the application of a model of value creation for use in systems of coproduced healthcare services and to evaluate the initial feasibility, utility and acceptability of associated system-level value creation assessment approaches. Issue 10 (5th October 2020) - Oliver, Brant J; Batalden, Paul B; DiMilia, Peter Rocco; Forcino, Rachel C; Foster, Tina C; Nelson, Eugene C; Garre, Boel Anderson
Abstract : Introduction: Coproduction introduces a fundamental shift in how healthcare service is conceptualised. The mechanistic idea of healthcare being a 'product' generated by the healthcare system and delivered to patients is replaced by that of a service co-created by the healthcare system and the users of healthcare services. Fjeldstad et al offer an approach for conceptualising value creation in complex service contexts that we believe is applicable to coproduction of healthcare service. We have adapted Fjeldstad's value creation model based on a detailed case study of a renal haemodialysis service in Jonkoping, Sweden, which demonstrates coproduction characteristics and key elements of Fjeldstad's model. Methods and analysis: We propose a five-part coproduction value creation model for healthcare service: (1) v alue chain, characterised by a standardised set of processes that serve a commonly occurring need; (2) v alue shop, which offers a customised response for unique cases; (3) a facilitated value network, which involves groups of individuals struggling with similar challenges; (4) interconnection between shop, chain and network elements and (5) leadership . We will seek to articulate and assess the value creation model through the work of a community of practice comprised of a diverse international workgroup with representation from executive, financial and clinical leaders as well as other key stakeholders from multiple health systems. We then will conduct pilot studies of a qualitative self-assessment process in participating health systems, and ultimately develop and test quantitative measures for assessing coproduction value creation. Ethics and dissemination: This study has been approved by the Dartmouth-Hitchcock Health Institutional Review Board (D-HH IRB) as a minimal risk research study. Findings and scholarship will be disseminated broadly through continuous engagement with health system stakeholders, national and international academic presentations and publications and an internet-based electronic platform for publicly accessible study information.